US foreign policy in the Middle East : the roots of anti-Americanism - Baxter, Kylie; Akbarzadeh, Shahram (London : Routledge, 2008)
This book covers US foreign policy in the Middle East from the mid-twentieth century to the present. It includes historical background on the Israeli/Arab Wars, Iran, intervention in Afghanistan and Iraq, the wars of the Persian Gulf, Israel Palestine, September 11 and the rise of Islamist movements. In particular the book charts how foreign policy decisions have led to the rise of Anti-Americanism in the region.
The Middle East in the colonial period -- Great power influences, Zionism and the Middle East -- Israel and the Arabs at war: superpower dimensions and the Israeli-US alliance -- Islamism and the Iranian revolution -- Proxy war: the superpowers in Afghanistan -- Wars in the Persian Gulf -- Israel and Palestine: the failure to find peace and the role of the United States -- The Iraq 'adventure' and Arab perceptions of the United States.
Includes bibliographical references and index.
Keywords: United States -- Foreign relations -- Middle East; Middle East -- Foreign relations -- United States; United States -- Foreign public opinion, Middle Eastern; Middle East -- Public opinion